LAYANAN BIMBINGAN KLASIKAL KELAS X SMA MUJAHIDIN PONTIANAK - Muhammad Rian Andani; Indri Astuti; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractClassic guidance service is one form of assistance for guidance and counseling services for students conducted in class format. The general problem of this research is "What is the Classical Guidance Service in Pontianak Mujahidin High School in 2018? (1) What steps are taken by the teacher of guidance and counseling in classical guidance services at Pontianak Mujahidin High School? (2) Materials provided by Guidance teachers and Counseling in Classical Guidance services at Pontianak Mujahidin High School? (3) What method is used by Guidance and Counseling teachers in Classical Guidance services at Pontianak Mujahdin High School? (4) What media are used by Guidance and Teacher Counseling Guidance in Classical Guidance Services in Schools Intermediate (5) What is the response of students after being given classical guidance services at SMA Mujahidin Pontianak? The method used was descriptive method with the form of survey research. Based on the results of analysis of class 10 classical guidance services in Pontianak Mujahidin High School, overall it reached 83% in the "Good" category. Keywords: Guidance and Counseling Services, Guidance Classical